Kurikulum Pendidikan di Indonesia dan Jepang: Sebuah Analisis Komperatif - Nur Hanifa; Mutiara Rahmi; Wan Muhammad Fariq; Muhammad Suprapto (STAIN Bengkalis, 2024)
Japan is recognized as having a superior education system in the world because of its complete facilities and competent human resources. Developing countries often point to Japan as an example for raising educational standards. This research aims to determine the comparison of educational curricula in Indonesia and Japan. The method used in this research is Literature Review, namely by conducting research on scientific articles, books and other sources that are relevant to certain problems, research fields, or theory, as well as several other documents that have been published. The results of this research are: 1) The level of education in Japan is the same as in Indonesia, consisting of nine years of basic education (primary school and junior high school), three years of senior high school (general and vocational tracks), and higher education, 2) The Japanese curriculum is revised every ten years, while the Indonesian curriculum is revised every time there is a change in leadership. 3) The general aim of education in Japan is similar to that in Indonesia, namely developing the potential of students. Japan's goals are more specific and include various characteristics that Japanese children must have. 4) The subjects taught in elementary school classes in Japan and Indonesia have significant differences, especially in terms of language and the variety of lessons taught. Apart from that, the learning approaches and curricula in the two countries also show striking differences, with different emphasis on language and certain skills. 5) The Indonesian curriculum adopts scientific methods and a project-based learning approach with teachers as facilitators, while the Japanese curriculum uses lesson study. with an open approach and problem solving, where the teacher acts as a facilitator with the principle that children must understand, can, and the class must be fun, 6) Both Indonesia and Japan do not apply the National Examination (UN) in assessment.